Implementation of A Blog-Based Journal Reading Strategy to Improve the Reading Comprehension Ability of UNIMED English Literature Students - Juli Rachmadani Hasibuan; Muhammad Natsir; Nazlah Syahaf Nasution; Lukman Nurul Hakim; Novita Permatasari Rangkuti; Stevany Silaban; Mazaya Zahira Harahap; Sumi Afrilia Ritonga (Randwick International of Education and Linguistics Science Journal, 2024)
This study explores the impact of a blog-based reading journal strategy on improving reading comprehension among English Literature students at Universitas Negeri Medan. Conducted over six months in 2024, the research involved 60 students who documented their reflections and analyses of assigned readings on blog platforms. The methodology included qualitative and quantitative approaches, with a rubric assessing comprehension, analytical skills, reflection depth, and coherence. Results showed significant improvement in reading comprehension, with 80% of students rating the overall experience highly and 100% finding the blog content very helpful. Critical and analytical thinking skills also improved, with 60% of students rating this aspect highest. Students were comfortable using the blog platform and suggested extending session durations and incorporating more visual aids. The study concludes that the blog-based strategy effectively enhances reading comprehension, engagement, and critical thinking, supporting its continued use and exploration in educational settings.